Analysis of the implementation of Blockchain as a mechanism for digital and transparent food traceability in Peruvian social programs - Perez D. (2020)
This paper studies the problems of the traditional food industry in Peruvian social programs, and how the Blockchain would serve as a solution that includes the immutable registration of information allowing the tracking of food by each responsible party in the process. It was observed that millions of people become ill or die from eating infected, spoiled, or intoxicated food and that these problems are directly linked to the registration and communication areas of the participants in the supply chain. It was concluded that combining technologies such as the Internet of Things (IoT) and Blockchain is an extremely attractive option for the transparent tracking of food from its production to its sale and consumption; likewise, using smart contracts ensures compliance with all the conditions necessary for its consumption. Finally, it should be mentioned that, by being able to track in seconds, the reduction of time and operating costs is imminent. © 2020 IEEE.